Sukuk Investment: Efficiency Of Global Sukuk Indices (based On Tenures) Following The 2008 Global Financial Crisis - Syazwani Abd Rahim; Nursilah Ahmad (Malaysian Financial Planning Council, 2024)
Non-Indexed Publication